2018
DOI: 10.1155/2018/4026831
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Chemical Properties of Edible Film Made from Soybean Residue and Citric Acid

Abstract: The effect of citric acid on the properties of soybean enzyme-assisted aqueous extraction processing (EAEP) residue edible film was studied. The washed soybean EAEP residue was produced by the process of EAEP. It was determined that the washed soybean EAEP residue is rich in fibers (76.10 ± 1.03%) and has lower oil and protein contents (7.74 ± 0.11% and 3.50 ± 0.20%, resp.). Edible films intended for food packaging have been produced from the washed EAEP residue combined with glycerol, different concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…As expected, aqueous solubility decreased with addition of CA up to 5% (w/w of total starch) level in the starch film. The outcomes are also consistent with previous studies (Ma et al 2018), who reported that solubility of the edible films containing soybean residue decreased with addition of citric acid. This dramatic influence of citric acid on the solubility of the starch film might be happened due to cross linking and hydrogen bonding among the functional groups of citric acid and starch chains.…”
Section: Solubility (S)supporting
confidence: 92%
“…As expected, aqueous solubility decreased with addition of CA up to 5% (w/w of total starch) level in the starch film. The outcomes are also consistent with previous studies (Ma et al 2018), who reported that solubility of the edible films containing soybean residue decreased with addition of citric acid. This dramatic influence of citric acid on the solubility of the starch film might be happened due to cross linking and hydrogen bonding among the functional groups of citric acid and starch chains.…”
Section: Solubility (S)supporting
confidence: 92%
“…The color index profile was evaluated by a CR-400 (Konica Co., Japan) for L*, a*, and b* values at three fixed locations on the mushroom caps 34 , 35 . The total color difference (ΔE) is reported by Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The color was detected by a ZE-6000 Meter (Nippon, Japan). D65 light source and an 8 mm diameter measuring area were used [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cantaloupe is an excellent vitamin C and β-carotene source; it also provides additional nutritional values of iron, potassium, and dietary fiber [ 4 ]. Some of the common and cost-effective methods are used for developing the quality of cantaloupe products includes the packaging by ultraviolet light [ 5 , 6 ], gamma radiation [ 7 ], chemical treatments [ 8 ], edible coatings [ 9 ], and multilayered edible coatings using nanotechnology [ 10 ]. This coating technique could be perfect for overcominge quality problems [ 11 ].…”
Section: Introductionmentioning
confidence: 99%